Team Approach: Spinopelvic Dissociation. Issue 8 (12th August 2021) - Wanner, John Paul; Tatman, Lauren; Stephens, Byron; Mitchell, Phillip
Abstract : » Spinopelvic dissociation is a complex and variable injury pattern that requires an integrated, multidisciplinary team including orthopaedic trauma and spine surgeons. » Protocols and efficient channels of communication should be in place at tertiary Level-I trauma centers to ensure appropriate and timely treatment of patients with spinopelvic dissociation. » Patients with spinopelvic dissociation may present with acute neurological deficits and impending cauda equina syndrome, necessitating urgent, coordinated care. » Lumbopelvic fixation with sacroiliac screws yields a stable, multiplanar construct that connects the spine to the pelvis and allows for early mobilization.